Phenotypic characterization of Trichosporon species from clinical isolates - T, Premamalini; S, Anitha; Priya K, Mohana; Jyoti Kindo, Anupma (International Journal of Medical Research and Review, 2018)
Introduction: Trichosporon spp. arepresent as normal flora of skin and perigenital area in humans. They can cause invasive trichosporonosis in immuno-compromised individuals. Trichosporon infections are difficult to treat, since they do not respond to routinely used antifungal agents. Aim: This study was undertaken to characterize clinical isolates of Trichosporonsp, using phenotypic methods. Material and Methods: Around 52 isolates of Trichosporon sp. obtained from various samples of patients in Sri Ramachandra Medical College & Research Institute, Chennai, were considered for the study. The isolates were studied for macroscopic morphology of the colonies on Sabouraud Dextrose Agar (SDA), microscopic morphology by Dalmau technique & Gram stain, ability to hydrolyze urea, sugar assimilation profile and growth at 37°C &0.1% cycloheximide. Results and Conclusion: Two types of colony morphologies were observed, 47 isolates appeared flat with farinose covering and 5 were cerebriform with radial fissures. All isolates hydrolysed urea, and none of the isolates fermented but only assimilated sugars. The Trichosporon isolates were identified up to species level by phenotypic methods. Still the reliability of identification has to be confirmed with genotypic characterization techniques.